Argumentation in speeches of communist leaders on the example of Tito, Stalin and Mao Tse-Tung - Kozina, Marta (Array, 2011)
The aim of this research which deals with rhetoric in political discourse was to depict specific argumentation techniques in the speeches given by famous communist leaders. The analysis of those speeches and their argumentation revealed typical elements of ideology in general. The fact that communist ideology and its impact on the modern society was explored in many sciences ; literature art, history, but was rarely analyzed from rhetorical perspective, motivated this research. This research includes the analysis of 4 Tito’s speeches, 3 Stalin’s and 2 Mao Tse-Tung’s speeches. Since they were all leaders of different and distant countries and belonged to different cultures, we were interested to see if the argumentation in their speeches was different or the shared communist ideology was strong enough to outgrow cultural differences of former Yugoslavia, SSSR and China. We were also interested to find out how often do speakers use fallacies in argumentation and which fallacy is the most frequent. The research was based on the theory of argumentation by Aristotle (1991.), Toulmin (1958.), Perelman (1982.), Weston (1992.), Fahnestock (1990.), Walton (2005.) and Tindale’s (2007) classification of fallacies. The results of the analyses show that there are some differences in argumentation among the speakers ; especially between Tito and Stalin on one side and Mao Tse-Tung on the other. Although they all frequently used similar fallacies, the most frequent in all speeches are: argumetum ad populum, generalizing from incomplete information, false cause, overlooking alternatives, red herring. We also found similarities in the vocabulary usage among the speakers, with frequent, use of words like socialism, communism, revolution, contra revolution, enemy, imperialism, capitalism, working class, propaganda.... It can be concluded that these communist leaders show great level of similarity indicated by the weak argumentation and frequent use of numerous fallacies in their speeches. However, some aspects of argumentation revealed differences resulting from different cultural heritage.